A case study of a small Kansas public charter school to identify school-level factors perceived to have contributed to student success - Kaiser, Carlene P. (Kansas State University, 2011)
The purpose of this research proposal was to investigate school-level factors identified by Marzano (2003) perceived to have contributed positively to student achievement in one charter school. The researcher noted the following issues related to charter schools and student achievement: The data on student achievement were mixed; limited research existed on student achievement using the school -level factors identified by Marzano (2003); limited case studies existed comparing school-level factors and student achievement for charter schools. Using the case study format, the researcher investigated perceptions regarding school-level factors perceived to have increased student achievement in one charter school in Kansas over a five-year period from 2005-2008. The case study was accomplished through the collection, analysis, and interpretation of data from multiple sources to include researcher observations, key informant interviews, and analysis of archival documents. After conducting the research, it was determined that while there wasn’t a deliberate attempt to use the factors by Robert Marzano (2003), the school-level factors were used by Dartmouth Charter School did impact student achievement as evidenced by stakeholder interview, Kansas Reading Assessments, and archival data sources. A case study confirmed the presence of several aspects of the school-level factors of a guaranteed/viable curriculum, challenging goals and effective feedback, parental and community involvement, a safe and orderly environment, and collegiality and professionalism, which were perceived by stakeholders as contributing to increased student achievement over the five-year period of operation.
Keywords: Charter schools; Student achievement; Student success; Case study; Marzano school-level factors; Kansas charter schools; Education, General (0515); Education Policy (0458)